Teaching Multiplication with Lesson Study - Isoda, Masami; Olfos, Raimundo (Springer Nature, 2021)
This open access book is intended to assist teachers, teacher trainers, curriculum designers, editors and authors of textbooks in developing strategies to teach the multiplication of natural numbers based on the experience of the Lesson Study in Japan. This approach to mathematics education dates back to the 1870s and reconciles the emphasis on problem solving with the treatment of the curricular contents. It has gained international recognition since the 1990s and thanks to it mathematics education in Japan has been recognized as one of the most efficient and innovative in the world. This growing international awareness has led to an effort to apply the principles of Lesson Study to other parts of the world and this book shows how experienced authors from Brazil, Chile, Mexico, Spain and Portugal have worked to adapt some of these methods and techniques to the Portuguese and Spanish speaking countries of Ibero-America. Drawing on the impact of Lesson Study on government curriculum decisions and teacher behavior in Japanese classrooms; offering examples of lessons, lesson plans and suggestions for teaching; and presenting examples of the good reception of the principles of Lesson Study in Ibero-America, Teaching Multiplication with Lesson Study – Japanese and Ibero-American Theories for Mathematics Education shows how an efficient and cutting-edge experience in mathematics education can travel the world and help teachers in many different countries. ; Shows how teachers can apply the principles of Japanese Lesson Study to teach the multiplication of natural numbers Presents an approach to mathematics education that reconciles the emphasis on problem solving with the treatment of the curricular contents Provides examples of how a method developed in Japan can be adapted to different cultural contexts, such as the Portuguese and Spanish speaking countries of Ibero-America